Pengaruh Penggunaan Media Sosial terhadap Interaksi Sosial dikalangan Mahasiswa - Harahap, Hilda Rahmadani; Turmuzi, Ahmad; Manik, Cindy Ramadhani; Valentina, Andini; Hafiz, Muhammad; Purba, Davina Zahwa (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2024)
The use of social media has become a significant phenomenon among college students today. Social media offers a platform to communicate, share information, and build relationships virtually. However, the impact of intensive use of social media on social interaction among students is still a matter of debate. This study aims to investigate how the use of social media affects social interaction among students. This study uses a quantitative approach by distributing questionnaires to a sample of students from various majors at several universities. The questionnaire was designed to collect data on the frequency of social media use, the types of social media used, and their social interaction patterns in daily life. Data analysis was carried out to determine the correlation between the variables of social media use and the level of social interaction among students. The results of the study showed that there was a significant correlation between the use of social media and student social interaction patterns. Students who use high-intensity social media tend to have more frequent social interactions through digital platforms compared to face-to-face interactions. However, social media use is also associated with a decrease in the ability to develop in-person interpersonal communication skills. In addition, the findings also show variations in the impact of social media use depending on the type of platform used, with visual social media such as Instagram tending to influence students' feelings and self-image more than text social media such as Twitter. The study provides a deeper understanding of how social media use affects social interaction among college students. The implications of this study highlight the need for a balanced approach to the use of social media in order to support the development of healthy and sustainable social interactions among students. Future research can further explore the psychological and social aspects of social media use to broaden our understanding of the dynamics of interpersonal relationships in this digital age.